Perspectives on the use of non-biological pharmacotherapy for adult-onset Still's disease. (22nd September 2022) - Di Cola, Ilenia; Cipriani, Paola; Ruscitti, Piero
ABSTRACT: Introduction: The treatment of the patients with adult-onset Still's disease (AOSD) remains largely empirical and it is based on the administration of immunosuppressive drugs. In this work, we described the use of non-biological pharmacotherapies for AOSD. Area covered: Although nonsteroidal anti-inflammatory drugs (NSAIDs) are employed during the diagnostic phase, glucocorticoids (GCs) are the first-line therapy, administered at the beginning of the disease. As second-line therapy, conventional synthetic disease modifying anti-rheumatic drugs (csDMARDs) are used when GCs do not fully control the disease and/or to reduce the dosage of concomitant GCs. Methotrexate (MTX) is the most commonly administered csDMARDs whereas calcineurin inhibitors (CNIs) are used in severe patients. The lack of achievement of clinical response may lead to the administration of biologic DMARDs, with or without csDMARDs. Expert opinion: The management of AOSD may benefit from the administration of non-biological pharmacotherapies, including GCs, MTX, and CNIs. These therapies showed efficacy in inducing a clinical response, in managing life-threatening complications, and may be well tolerated in combination with biologic DMARDs. However, further specific studies are needed to fully clarify the specific role of such drugs in clinical practice to improve the management of AOSD and to provide a more tailored treatment.